The Relationship between International Law and Domestic Law and Its Applications in Iraqi and Jordanian Law - Al-Mohammadi, Adel (Journal of Legal Sciences, 2025)
The research dealt with defining international and domestic law and its trends in the first section. In the second section, the research dealt with the theories of the two laws, and in the third section, the position of international law on the Iraqi and Jordanian legal system. I divided the first section into two requirements: The first was to define public international law as a branch of legal science and how scholars differed in naming this law. Some called it) the law of nations) and some called it) the law of peoples). I explained its trends, which are the classical trend )which is a group of legal rules that regulate relations between states, and it is concerned with regulating rights and duties) and the objective trend)Which considered the individual to be the only person of international law, who has the will, and that the legal personality of the state is merely an assumption that has no reality in existence) and the modern trend) which is to combine in their definition of international law the state and other persons of international law) In the second section, I defined internal law and explained the definition of legal scholars and philosophers, which is a formula for social behavior patterns. In a narrower definition, it is: a set of binding rules that govern the complex relationships of people living in society. In the second section, I discussed the theories of international and domestic law, where I explained in the first section the theories of the two laws, which are: )the theory of duality: which means making the rules of public and domestic international law one block, i.e. a legal system that is not separate from each other) and the theory of )the unity of law: which is the opposite of the previous theory and considers each law separate from the other, and is based on the idea of legal gradation). On this basis, the supporters of the theory of the unity of law were divided into two directions) The first is the proponents of the theory of the unity of law and the supremacy of domestic law, and the theory of the unity of law and the supremacy of international law), and in the second requirement I showed the conformity of the two laws with the constitutions of the countries and its position on the Iraqi and Jordanian law. I showed in it that as a result of the contradiction between the theory of duality and the theory of the unity of law, the practical applications also differed through) international relations, international judiciary, and the constitutions of the countries). In the third section, I explained the position of international law on the Iraqi and Jordanian legal system, and explained the constitutional articles and laws in both countries.